CROWDFUNDING-WAQF DAN GENERASI MILENIAL: ANALISIS BERDASARKAN PENDEKATAN UTAUT - Qonitah Rifda Zahirah; Muhammad Dandy Alif Wildana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Waqf has significant potential in Indonesia because the majority of its population is Muslim. However, the development of waqf is hindered by issues related to fund allocation and distribution, as well as inefficiencies in traditional waqf. This study aims to analyze the intentions of Millennials in conducting Crowdfunding Waqf using the Unified Theory of Acceptance and Use of Technology (UTAUT) model, supplemented with variables such as religiosity, information media, knowledge, and altruism. Primary data were collected through an online survey in Malang City with 253 respondents who are Muslim, belong to the millennial generation, are residents of Malang City, and are employed. The analysis was conducted using SEM-PLS (Partial Least Squares-Structural Equation Modelling). The results show that the variables of performance expectancy, effort expectancy, information media, altruism, and knowledge level have a positive and significant relationship with millennials' intentions to conduct crowdfunding waqf. Conversely, the variables of social influence, facilitating conditions, and religiosity have a positive but not significant relationship with these intentions. This study makes an important contribution to the literature on factors influencing the acceptance and adoption of waqf-based crowdfunding models among millennials. Keywords: Crowdfunding Waqf; Millennial Generation; UTAUT